2019
DOI: 10.1021/acs.jafc.9b03073
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Characterization and Substrate Degradation Mode of a Novel α-Agarase from Catenovulum agarivorans

Abstract: Agarose can be hydrolyzed into agarooligosaccharides (AOSs) by α-agarase, which is an important enzyme for efficient saccharification of agarose or preparation of bioactive oligosaccharides from agarose. Although many β-agarases have been reported and characterized, there are only a few studies on α-agarases. Here, we cloned a novel α-agarase named CaLJ96 with a molecular weight of approximately 200 kDa belonging to glycoside hydrolase family 96 from Catenovulum agarivorans. CaLJ96 has good pH stability and ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Thus, polysaccharide lyases and glycosyl hydrolases were isolated from microorganisms, including fungi and bacteria. The genus Catenovulum have been known as bacteria that can degrade agar and polysaccharide containing uronic acids, such as alginate, pectin, and ulvan (Cui et al, 2014;Li et al, 2015;Lee, Lee & Hong, 2019;Liu et al, 2019a;Xie et al, 2013). Our previous report demonstrated that many genes encoding polysaccharide-degrading enzymes were present in the QB4 genome (Lau et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, polysaccharide lyases and glycosyl hydrolases were isolated from microorganisms, including fungi and bacteria. The genus Catenovulum have been known as bacteria that can degrade agar and polysaccharide containing uronic acids, such as alginate, pectin, and ulvan (Cui et al, 2014;Li et al, 2015;Lee, Lee & Hong, 2019;Liu et al, 2019a;Xie et al, 2013). Our previous report demonstrated that many genes encoding polysaccharide-degrading enzymes were present in the QB4 genome (Lau et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Agarases play a key role in the preparation of specific agaro-oligosaccharides. According to the glycosidic bonds they cleave in agarose, agarases can be divided into α-agarase of cutting α-1,3-glycosidic linkage and β-agarase of cutting β-1,4-glycosidic linkage to produce agarooligosaccharides (AOS) and neoagarooligosaccharides (NAOS) from hydrolysis of agarose, respectively. , Therein, several α-agarases have been identified and characterized; all of them belong to the glycoside hydrolase (GH) 96 family. Compared with α-agarases, the β-agarases were explored more exhaustive, so far, over 50 β-agarases has been expressed heterologous. , These characterized β-agarases belong to four GH families, including GH16, GH50, GH86, and GH118. Therein, the β-agarases of GH16 and GH50 were most identified.…”
Section: Introductionmentioning
confidence: 99%
“…Among the many agarases reported, most are β-agarases, except some α-agarases isolated from Alteromonas agarilyticus GJ1B [15], Thalassomonas agarivorans JAMB-A33, Catenovulum agarivorans [16], and Caternovulum sediminis WS1-A [17]. Several reports have described that β-agarases hydrolyze agarose to produce various neoagaro-oligosaccharides, such as neoagarobiose, neoagarotetraose, and neoagarohexaose [1].…”
Section: Introductionmentioning
confidence: 99%